SOL-GEL DERIVED Co AND Ni BASED CATALYSTS: APPLICATION FOR STEAM REFORMING OF ETHANOL - Haryo Satriya Oktaviano; Wega Trisunaryanti (Universitas Gadjah Mada, 2008)
Cobalt and nickel based catalysts for ethanol steam reforming have been prepared. Preparation of Na-Ni-Mo/C, Na-Co-Mo/C, K-Ni-Mo/C and K-Co-Mo/C have been carried out using sol-gel method by applying citric acid as complexion agent and source for support formation. Prepared catalyst via sol gel showed tailored morphological properties signed by tailored pore size distribution. The acidity of catalyst showed that all catalysts contain only Lewis acid site. The catalyst activity test was conducted by using semi flow method with molar ratio of ethanol : water = 0.33 at 400 oC